Interpersonal Communication and Work-Life Balance: Key Drivers of Contract Employee Performance - Ari Awaludin; Nandang Nandang; I Dewa Gede Sayang Adi Yadyana (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
This study aims to analyze the effect of interpersonal communication (X1) and work-life balance (X2) on the performance of contract employees in the AC Division of PT Sharp Electronics Indonesia. Using a quantitative approach with a survey method, this study involved 50 contract employees as respondents, with data collected through questionnaires. Data analysis was conducted with multiple linear regression, t test, and F test to evaluate partial and simultaneous effects. The results showed that interpersonal communication and work-life balance have a significant effect on individual employee performance. Good communication enhances collaboration and productivity, while a maintained work-life balance supports well-being and motivation. However, when the two variables were analyzed together, they had no significant effect on performance, with a coefficient of determination of only 7.9%, indicating the presence of other factors affecting performance. Based on these findings, it is important for companies to improve interpersonal communication and support work-life balance to optimize employee performance. Therefore, companies need to design communication training programs and work flexibility policies.